Atherosclerotic aortic aneurysm in a steppe eagle (Aquila nipalensis). Issue 1 (20th August 2015) - Abou‐Zahr, Tariq; Dutton, Thomas Anthony George; Calvo Carrasco, Daniel; Forbes, Neil; Stidworthy, Mark Frederick
Abstract : A 23‐year‐old female imprinted steppe eagle ( Aquila nipalensis ) was presented by a public falconry centre for postmortem examination following sudden death with no previous clinical signs. Postmortem examination revealed the presence of 150 ml of blood within the coelomic cavity, with a packed cell volume of 42% indicating an acute, internal haemorrhage as a presumptive cause of death. A well‐demarcated, solid, hard, ovoid, approximately 3 cm×2 cm (in cross section) mass was discovered within the body of the aorta adjacent to the ovary. Histological examination confirmed this to be an aortic aneurysm underlain by severe atherosclerosis with a transmural rupture.